Principles of fermentation technology - Stanbury, Peter F. (Elsevier, 2017)
The successful structure of the previous edition of Principles of Fermentation Technology has been retained in this third edition, which covers the key component parts of a fermentation process including growth kinetics, strain isolation and improvement, inocula development, fermentation media, fermenter design and operation, product recovery, and the environmental impact of processes. This accurate and accessible third edition recognizes the increased importance of animal cell culture, the impact of the post-genomics era on applied science and the huge contribution that heterologous protein production now makes to the success of the pharmaceutical industry. This title is ideally suited for both newcomers to the industry and established workers as it provides essential and fundamental information on fermentation in a methodical, logical fashion. Stanbury, Whitaker and Hall have integrated the biological and engineering aspects of fermentation to make the content accessible to members of both disciplines with a focus on the practical application of theory. This text collates all the fermentation fundamentals into one concise reference, making it a valuable resource for fermentation scientists, as well as those studying in the field.--